2019
DOI: 10.1590/2179-8087.070317
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Height Growth in Tectona grandis Plantations in Mato Grosso, Brazil

Abstract: Tectona grandis (teak) plantations have gained increased interest in recent decades in Brazil, bringing about the need for acquiring information regarding the growth and productive potential. The present work aims to evaluate the growth of dominant height in teak at various locations in the state of Mato Grosso, midwest Brazil. For this purpose, six stands were evaluated in distinct municipalities and the database was obtained from trunk analysis. Subsequently, the dominant height growth was estimated using no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It applies the F-test to the statistic given by the ratio between the mean square of the difference of the complete model and the reduced model, and the mean square of the complete model. Each spacing in question was fitted in an equation for comparison purposes in order to obtain the complete model, according to procedures described by Vendruscolo et al (2019a).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…It applies the F-test to the statistic given by the ratio between the mean square of the difference of the complete model and the reduced model, and the mean square of the complete model. Each spacing in question was fitted in an equation for comparison purposes in order to obtain the complete model, according to procedures described by Vendruscolo et al (2019a).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Teak plantations in Brazil have obtained higher silvicultural yields than those in natural areas, reducing the rotation cycle from 80 to 25 years (Tsukamoto et al 2003). Studies have reported higher growth in diameter at breast height (DBH) and dominant height in forest stands in Brazil when compared to stands in India, Indonesia, and Ghana (da Conceicao et al 2012;Pelissari et al 2013;Vendruscolo et al 2019). These results are largely related to the advanced silvicultural methods used in forest plantations in Brazil and the adaptation of the species to the local edaphoclimatic conditions.…”
Section: Introductionmentioning
confidence: 99%